A monitoring-based approach for WSN security using IEEE-802.15.4/6LowPAN and DTLS communication. (5th July 2019) - Fuentes-Samaniego, Raul A.; La, Vinh Hoa; Cavalli, Ana Rosa; Nolazco-Flores, Juan A.; Ramirez-Velarde, Raul V.
In this paper, we present a monitoring-based approach for securing upper layer communications of wireless sensor networks (WSN), the latter using IEEE802.15.4/6LoWPAN stacks and tinyDTLS. The monitoring techniques have been integrated as an extension to the industrial tool Montimage monitoring tool (MMT). The MMT-extension verifies that the network is working following a set of security rules that have been defined by ETSI. The security rules check if the protocol stack is working properly. If MMT detects a security rule that was not respected, then it sends an alarm to the system manager so that he can take properly reactive adjustments. We tested each of the security rules in MMT's extension using point-to-point configuration. After all these tests were verified, we tested our MMT-extension using real data gathered from the FIT IoT-LAB platform. The results of these tests shown that our MMT's extension for WSN using IEEE-802.15.4/6LowPAN and DTLS communication is feasible.